温柔的使命: 生態, 信仰, 生活的結合 - Lin, Yiren, author; Chen, Tzu-Mei, author; Taiwan Ecological Stewardship Association, publisher (Colorado State University. Libraries, 2016)
Article 1: In his sermon preached June 5, 2016, at the Ho-Ping Church in Taipei, Rolston emphasized that, like ancient Israel, all peoples today reside on lands with promise, promised lands. Taiwan was long known as Formosa, the beautiful island. Americans sing "America, the Beautiful." Earth is a planet with great promise; such planets are rare in the universe. The main theme of ecological ethics is homing. We are all "Earth gardeners" who have a divine destiny to "care for the Earth," our home planet.

Article 2: During his three visits to Taiwan, in 2004, 2008, and 2016, Dr. Rolston has given 45 lectures. TESA set the theme of these 45 lectures according to the contents of Rolston's books, from Philosophy Gone Wild, Science and Religion, to Environmental Ethics to A New Environmental Ethics: The Next Millennium for Life on Earth. In Taiwan, we would like to keep on promoting what we have learned from his messages in his books and his life.
Gentle mission: integrated ecology, faith and living
Article 1. 找家 -- 羅 斯頓的生態哲學
Article 1. 找家--羅斯頓的生態哲學 [Looking for home -- Rolston's Ecology and Philosophy] / 林益仁 [Yiren Lin] -- Article 2. 從 [被解聘的鄉下牧師] 到 [環境倫理學之父] [From "dismissed country preacher" to "the father of environmental ethics"] / 陳慈美 [Tzu-mei Chen].
Keywords: Rolston, Holmes, 1932-2025; Earth as promised land; Earth as planet with promise; home planet; Taipei; Taiwan; Taiwan Ecological Stewardship Association